How Do E-Portfolios Influence Students' Cognitive Development? A Qualitative Exploration toward the implementation of E-portfolio - Br Kaban, Gres Desika; Kusuma, I Putu Indra; Indrayani, Luh; Hashim, Haida Umiera (Universitas Pendidikan Ganesha, 2025)
The advancement of technology has supported the implementation of e-portfolios in students speaking performance, which can be described as a digital tool where students can collect and store their projects online for quick access as long as their devices have an internet connection. However little is known has qualitatively explored how e-portfolio influence students’ cognitive development in relation to their speaking performance. It is thereby leading to a lack of literature on this topic. This research, therefore, aims to examine how e-portfolios will influence cognitive development in students’ speaking performance using a qualitative method. A phenomenological qualitative study design consisting of note-taking and semi-structured interview methods was used to obtain data from 33 eleventh-grade students ranging between 17-18 years old. The interview data were analyzed using inductive thematic analysis; meanwhile, the note-taking was analyzed using content analysis to support the thematic analysis. The result showed that the students had a cognitive development on their speaking performance in terms of pronunciation, vocabulary, and fluency. Moreover, students showed the benefits of peer feedback in e-portfolio activities, which enhanced their awareness and led them to identify strengths and weaknesses as well as to recognize the area for improvement in their speaking performance.